2016
DOI: 10.1016/j.addr.2015.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Matricellular proteins in drug delivery: Therapeutic targets, active agents, and therapeutic localization

Abstract: Extracellular matrix is composed by a complex array of molecules that together provide structural and functional support to cells. These properties are mainly mediated by the activity of collagenous and elastic fibers, proteoglycans, and proteins such as fibronectin and laminin. ECM composition is tissue-specific and could include matricellular proteins whose primary role is to modulate cell-matrix interactions. In adults, matricellular proteins are primarily expressed during injury, inflammation and disease. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 287 publications
(245 reference statements)
1
28
0
Order By: Relevance
“…For example, cadherin‐11 affects the activity levels of crac1 and STAT 3, which in turn regulates the P53 signaling pathway . Proteoglycans have an indispensable role in the tumor microenvironment, and as a result, many studies have described their potential use as target genes, biomarkers, and active agents . Moreover, it has been found that mutations in cell cycle genes can affect the differentiation of squamous cells in the course of modern anticancer treatment research .…”
Section: Discussionmentioning
confidence: 99%
“…For example, cadherin‐11 affects the activity levels of crac1 and STAT 3, which in turn regulates the P53 signaling pathway . Proteoglycans have an indispensable role in the tumor microenvironment, and as a result, many studies have described their potential use as target genes, biomarkers, and active agents . Moreover, it has been found that mutations in cell cycle genes can affect the differentiation of squamous cells in the course of modern anticancer treatment research .…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence stressing the important role of the ECM in the regulation/modulation of the inflammatory process (Toole, 2004; De Bock et al, 2015; Murai, 2015; Schwertfeger et al, 2015; Sawyer and Kyriakides, 2016). For example, versican, hyaluronan and other components of the ECM such as fibronectin or laminin, have been shown to interact with resident cells during inflammation, contributing to their proliferation and migration (Gee et al, 2004; Petrey and de la Motte, 2014; Andersson-Sjöland et al, 2015; Schwertfeger et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Distinct actions of matricellular protein fragments further complicate therapeutic implementation. Identification of the functional domains responsible for specific protective or detrimental matricellular actions is needed in order to design peptide-based strategies that simulate these effects (12,135).…”
Section: The Cardiac Ecm In Metabolic Diseasementioning
confidence: 99%